EFEKTIVITAS DANA SUBSIDI LANGSUNG TUNAI (SLT) DALAM MENGATASI DAMPAK KENAIKAN HARGA BBM BAGI MASYARAKAT MISKIN (Forum Ilmu Sosial, 2008)
Subsidi Langsung Tunai (SLT) is one of the government programs to help poor people to face theeffect of the increasing of gas price policy. The data of the receivers collect from BPS’s list. Governmenthopes that the effect of the increasing price of gasoline do not give impact to the increasing number ofpoor people. The distribution of SLT was done periodically each three months, begins on October 2005until September 2006. The SLT assistance distributed in cooperation with the post office across thecountry which reach the remote area. The SLT receivers confessed that this program is very helpful forthem in fulfilling their daily needs in the difficult situation recently. There are various uses of the SLT’sassistance among the receivers. Most of them spent the assistance for consuming daily needs, payingeducation cost, buying medicine, paying debt and other social activities such as for charity. The SLTdistribution done by the government was not effectively helping poor people. They have already spent theassistance just only in one or two weeks. Implementing the SLT assistance program like this is such asSanta clause model which can give bad physiological impact for instance laziness and dependency amongthe receiver to the government. There for reevaluation is needed for the type of assistance, distributionmodel and other related technical factors, so that in the future the government assistance for poor peoplecan be used effectively and optimally.Keywords: SLT assistance, gasoline, poor people, effective.